A new species of Decimoconularia (Cnidaria, Medusozoa) from the Lower Cambrian of South China - Song, Zuchen; Guo, Junfeng; Han, Jian; Van Iten, Heyo; Qiang, Yaqin; Peng, Jiaxin; Sun, Jie; Zheng, Yajuan; Huang, Xinyao; Zhang, Zhifei (Frontiers in Earth Science, 2023)
Hexangulaconulariids, a family of biradially symmetrical, medusozoan cnidarians, have been widely reported from the Lower Cambrian of South China. The four currently recognized genera of hexangulaconulariids differ from each other mainly in the number of faces in the abapical region of the periderm. However, previously published illustrations of the monospecific type genus, Hexangulaconularia, clearly encompass two distinct morphotypes, one with six faces and the other with 10. Specimens with 10 faces are herein reassigned to the genus Decimoconularia. In addition, the new species D. anisfacialis is described from the Kuanchuanpu Formation (Cambrian Fortunian Stage) in the Kuanchuanpu and Shizhonggou sections in Ningqiang County, southern Shaanxi Province, China. Also described are additional specimens of H. formosa from the same formation in the Zhangjiagou section in Xixiang county, southern Shaanxi Province and from Member 2 of the Yanjiahe Formation (Cambrian Fortunian Stage) in western Hubei Province. The discovery of D. anisfacialis extends the stratigraphical range of Decimoconularia, now composed of two species, downward from Cambrian Stage 2 into the Fortunian Stage. Additionally, certain specimens previously assigned to H. formosa are reassigned to D. anisfacialis. The diagnoses of Hexangulaconularia, Decimoconularia, and Hexangulaconulariidae are emended accordingly. In accordance with the rule of time priority, the previously designated type genus and species, Hexaconularia He and Yang, 1986 and Hexaconularia sichuanensis He and Yang, 1986, are replaced herein by Hexangulaconularia He, in Xing et al., 1983 and Hexangulaconularia formosa He, in Xing et al., 1983.